2019
DOI: 10.1136/jim-2019-001075
|View full text |Cite
|
Sign up to set email alerts
|

Peptide growth factors and their receptors in the vein wall

Abstract: The varicose vein wall remodeling is a very complex process, which is controlled by numerous factors, including peptide growth factors. The aim of the study was to assess a/b FGF, IGF-1, TGF-β1, VEGF-A and their receptors in the vein wall. Varicose vein samples were taken from 24 patients undergoing varicose vein surgery. The control material consisted of vein specimens collected from 12 patients with chronic limb ischemia. Contents of aFGF, bFGF, IGF-I, TGF-β1, VEGF, IGF-1R, VEGF R1 and VEGF R2 were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Afterwards, many researches have shown that IRS4 phosphorylates PI3K, therefore being a direct inductor of PI3K/Akt/mTOR pathway 53 , 54 . The overexpression of IGF-1 and PI3K/Akt/mTOR has been involved in the pathogenesis of vascular wall inflammation and aging 55 , 56 . Interestingly, In human placenta, enhanced IGF-1 levels have been associated to increased PI3K/Akt/mTOR pathway activity and subsequent alterations in placental protein synthesis, mitochondrial function and nutrient transport 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, many researches have shown that IRS4 phosphorylates PI3K, therefore being a direct inductor of PI3K/Akt/mTOR pathway 53 , 54 . The overexpression of IGF-1 and PI3K/Akt/mTOR has been involved in the pathogenesis of vascular wall inflammation and aging 55 , 56 . Interestingly, In human placenta, enhanced IGF-1 levels have been associated to increased PI3K/Akt/mTOR pathway activity and subsequent alterations in placental protein synthesis, mitochondrial function and nutrient transport 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, a local response to the altered environment will be developed, with remarkable changes in the different layers. In this sense, significant changes in peptide growth factors and their receptors have been identified in the venous wall of patients with CVD, including acidic fibroblast growth factor (aFGF), VEGF, and insulin-like growth factor 1 (IGF-1), and its receptor (IGF-1R) [ 198 ]. The last route appears to be particularly important in the venous wall of patients with CVD, where we have recently reported an altered homeostatic IGF-1/PAPPA/STC-2 axis [ 199 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…This route is hyperactivated during hypoxia and promotes the activity of different components involved in the metabolic reprogramming of proliferative cells, for instance through the activation of the enzyme ALD [39] or the proper PGK1 [40], negatively regulated by the natural inhibitor of PI3K pathway, PTEN. The importance of these components was found in the venous walls of VVs [41,42], so it is likely that the alteration of these components might be implicated in the changes occurred in the placenta of women with CVD. Furthermore, we have observed a significant increase of GA3PDH and the isoform LDHA in the placenta of women with CVD.…”
Section: Discussionmentioning
confidence: 99%
“…62 were diagnosed with CVD, with an average age of 33 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and a median gestational time of 40.5 [39-41.5] weeks for all clinical and histological studies. Likewise, 52 control women with no presence of CVD (HC) were studied, with a median age of 34 [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] years and a median gestational time of 41 [39][40][41][42] weeks for all clinical and histological studies. This study has been conducted following the four basic ethical principles: Autonomy, beneficence, non-maleficence and distributive justice.…”
Section: Study Populationmentioning
confidence: 99%